Advances of cardiovascular MRI in hypertrophic cardiomyopathy. (September 2013) - Kumar, Preetham; Blackshear, Joseph L; Ibrahim, El-Sayed H; Mergo, Patricia; Parikh, Pragnesh; Batton, Kyle; Shapiro, Brian
Hypertrophic cardiomyopathy (HCM) is a genetic disease characterized by abnormal myocardial hypertrophy, which can lead to a wide clinical spectrum, including sudden cardiac death and heart failure. Cardiac MRI has a significant role in establishing the diagnosis of HCM. In the three principal management issues related to HCM; testing of family members of affected individuals; assessing the risk of sudden cardiac death from lethal ventricular arrhythmias; and selection of appropriate treatments for left ventricular outflow obstruction, cardiac MRI has established or emerging roles.